Self-expandable stents for benign esophageal leakages and perforations: long-term single-center experience. (January 2013) - Gubler, Christoph; Bauerfeind, Peter
Abstract Objective. To date, there is no standardized treatment for esophageal perforations and leakages caused by underlying benign diseases, and it is still debated whether a conservative, endoscopic treatment or a surgical approach is preferable. However, some cases series have successfully demonstrated the feasibility of a temporary placement of self-expanding stents. Design. All patients with benign leakages of the esophagus or gastroesophageal junction or fistulas at gastroesophageal anastomosis were collected during the past 12 years and analyzed retrospectively. The patients treated with endoscopic stenting were analyzed for sustained success, complications, time to stenting, lesion size, number of stents used, need for percutaneous drainage. Results. Eighty-five of eight-eight patients were included in this analysis. Three patients were conservatively managed only. The success rate of stent treatment with an average of 1.3 stents was 79%. Success was highest (94%, n = 30 of 32, no complications or mortality) in iatrogenic lesions that were immediately diagnosed and treated. Spontaneous lesions, including lesions due to Boerhaave's syndrome, were healed in 73% and anastomotic leakages were closed in 71%. Fistula had a lower success rate of 43%. Use of multiple stents sequentially placed was necessary in 23% of the cases. Percutaneous drainage was necessary in 25% of all cases. Conclusion. Temporary stent placement for benign leakages of the esophagus is safe and seems to improve treatment success. Adjacent fluid collections should be drained percutaneously.